Mogroside, palatinose, erythritol, and xylitol differentially affect dental plaque pH in caries-active and caries-free children: An in vitro study - Palinthorn Nagsuwanchart (2022)
Objective: To investigate the effect of mogroside, palatinose, erythritol, and xylitol on the dental plaque pH of children and to compare the plaque pH change between caries-active and caries-free children caused by these sweeteners. Methods: Thirty-six children (mean age 6.2 ± 2.9-year-old), caries-active and caries-free, were included. After refraining from practicing oral hygiene, the accessible plaque was collected and equally divided for challenging with 6 different solutions: mogroside, palatinose, erythritol, xylitol, 10% sucrose, and deionized water. The pH of each solution was measured using a digital pH meter at 0, 5, 10, 15, 20, 25, and 30 min. Results: Mogroside, erythritol, xylitol, and water did not significantly lower the dental plaque pH, however, palatinose reduced dental plaque pH comparable to sucrose (p < 0.05). Comparing the caries-active and caries-free groups, only sucrose produced significantly different pH value at min 5 and 10. Conclusions: Mogroside, erythritol, and xylitol did not lower the dental plaque pH in caries-active or caries-free children. However, palatinose affected the dental plaque pH similar to sucrose.